Achilles tendinopathy prevention: An evidence-based approach - Joshua Sargeant; Victor Romano (spdfharmony.com, 2025)
Background: Achilles tendinopathy is a common musculoskeletal disorder causing pain and impaired tendon function, primarily affecting athletes and individuals engaged in repetitive activities like running and jumping. It progresses through stages of tendon health, disrepair, and degeneration, often leading to chronic overuse injuries. Aims: This study aims to identify evidence-based prevention and management strategies by analyzing intrinsic factors (e.g., flexibility, muscle strength, tendon stiffness) and extrinsic factors (e.g., training loads, footwear). It proposes an integrated prevention framework that combines biomechanical, physiological, and contextual risk factors to guide athletes, coaches, and healthcare professionals. Methods: A systematic review of 250 studies from PubMed, Scopus, Google Scholar, and Consensus AI resulted in the selection of 34 high-quality studies. The review focused on Achilles tendinopathy prevention and management strategies, particularly exercise interventions, load management, and biomechanical factors. Results: The findings highlight the importance of intrinsic and extrinsic factors in reducing tendinopathy risk. Key strategies include eccentric calf exercises, dynamic and static stretching, targeted strength training, optimized load management, and biomechanical interventions such as footwear modification. Unlike previous studies that examined these components separately, this research presents a comprehensive prevention framework. Conclusion: This study integrates multiple risk factors into a cohesive model for Achilles tendinopathy prevention. It emphasizes the necessity of a multidimensional approach over isolated interventions. Future research should focus on experimental validation and longitudinal studies to assess the long-term effectiveness of this framework across diverse populations.